Clases virtuales y su impacto en el aprendizaje de los estudiantes de bachillerato de la Unidad Educativa Enrique Ponce Luque del cantón Quevedo, año 2022 - Ruiz Duarte, Valeria Susana (2022)
The new pedagogical models require significant changes in their results so that they efficiently meet the objectives of the Education System, which is why it is necessary for the student and teacher to be trained. One of the problems that has arisen is that some of the students of the Educational Unit were not used to the virtual class process. The objective of this research is to determine the impact that virtual classes have had on the learning of high school students of the "Enrique Ponce Luque" Educational Unit of the Quevedo canton; For the development of the investigative process, the survey technique was used through which a questionnaire of easy-to-understand questions was developed, which was applied to the students, to obtain the size of the sample, we proceeded to take randomly from the total number. of students through which it was concluded that virtual education has allowed the student to understand better than technology, giving him the privilege of knowing a universe of possibilities in learning making it easier, communicative and participatory.